1999
DOI: 10.1007/s003600050260
|View full text |Cite
|
Sign up to set email alerts
|

Thermal sensitivity of mitochondrial function in the Antarctic Notothenioid Lepidonotothen nudifrons

Abstract: The thermal sensitivity of mitochondrial function was investigated in the stenothermal Antarctic ®sh Lepidonotothen nudifrons. State 3 respiration increases with increasing temperature between 0°C and 18°C with a Q 10 of 2.43±2.63. State 4 respiration in the presence of oligomycin, an inhibitor of mitochondrial ATP synthase, quanti®es the leakage of protons through the inner mitochondrial membrane, which causes oxygen consumption without concomitant ATP production. This parameter shows an unusually high Q 10 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
71
2

Year Published

2001
2001
2013
2013

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 76 publications
(90 citation statements)
references
References 37 publications
17
71
2
Order By: Relevance
“…The oxidation system was highly coupled with the phosphorylation system in Pleuragramma antarcticum at temperatures of 5°C and 10°C, where RCR values reached 12.35 ± 0.79 (n = 10, ± SE) and 12.66 ± 1.26 (n = 8, ± SE), respectively (Figure 1). These values are among the highest reported for notothenioid liver mitochondria (Hardewig et al 1999a). No significant differences were found among RCR values obtained between 5°C and 15°C (one-way ANOVA, P > 0.05).…”
Section: Thermal Tolerance In Mitochondria Of Pleuragramma Antarcticummentioning
confidence: 47%
See 4 more Smart Citations
“…The oxidation system was highly coupled with the phosphorylation system in Pleuragramma antarcticum at temperatures of 5°C and 10°C, where RCR values reached 12.35 ± 0.79 (n = 10, ± SE) and 12.66 ± 1.26 (n = 8, ± SE), respectively (Figure 1). These values are among the highest reported for notothenioid liver mitochondria (Hardewig et al 1999a). No significant differences were found among RCR values obtained between 5°C and 15°C (one-way ANOVA, P > 0.05).…”
Section: Thermal Tolerance In Mitochondria Of Pleuragramma Antarcticummentioning
confidence: 47%
“…When extrapolated to 0°C, N. coriiceps liver mitochondria exhibited lower state III rates than observed in red muscle tissue of N. coriiceps and livers mitochondria of other notothenioids (Johnston et al 1994;Johnston et al 1998;Mark et al 2012). However, state III rates of the conspecifics L. squamifrons and L. nudifrons (Hardewig et al 1999a) were found to be significantly different. These differences were expected due to differences in the titration protocol: values for L. nudifrons corresponded to state III rates in the presence of only succinate, ADP and the complex I inhibitor rotenone.…”
Section: Antarctic Teleostsmentioning
confidence: 96%
See 3 more Smart Citations